An Information Systems Study on the Tuition Loan System of the University of the Philippines Diliman, Quezon City - Alava, Geraldine; Arguelles, Cristina; Elevado, Ma. Elissa; Fernandez, Marnie; Gerena, Juan Carlos (College of Engineering, 1988)
Aside from academic programs, students of the University of the Philippines can take advantage of various services and facilities. One such service is the Student Loan. Loans are granted by the University through the Student Loan Board to any enrolled student regardless of what he is in, but only for matriculation fees. Students generally associate university processes with queues and delays. The experience of one of the group members with regards to the Loan Board is no different. This study was undertaken as an academic exercise ? to apply the methods learned though IE 54 and other Industrial Engineering courses on a site the group, as students, can easily relate to. Hopefully, the members of the group will no longer be around to avail of the loan service, but for the many other students an improvement in the services extended by the Board would be greatly appreciated.